Effects of workaholism on volunteer firefighters' performance: a moderated mediation model including supervisor recognition and emotional exhaustion. Issue 5 (3rd September 2019) - Sandrin, Émilie; Gillet, Nicolas; Fernet, Claude; Depint-Rouault, Clément; Leloup, Monique; Portenard, Dominique
ABSTRACT: Background and Objectives: Although workaholism has been associated with job performance, the mechanisms that explain this relationship remain unclear. In this study, we investigated the conditional indirect effects of workaholism on performance via emotional exhaustion, across low and high levels of supervisor recognition. Methods: We conducted an empirical cross-sectional study using a sample of 1028 volunteer firefighters who completed a self-report questionnaire assessing workaholism, emotional exhaustion, work performance, and supervisor recognition. Results: Tests of latent interactions were performed using the latent moderated structural equation modeling approach. Consistent with our predictions, results revealed that the negative indirect effects of workaholism on performance, through emotional exhaustion, were stronger when supervisor recognition was low. Conclusions: Theorical contributions and perspectives, as well as implications for practice are discussed.